Taste masking study of cocoa butter fast melt tablet (FMT) formulations containing memantine hydrochloride - Liew, Kai Bin; Chew, Yik Ling; Helal Uddin, A.B.M.; Lee, Siew-Keah; Lakshminarayanan, Vijayakumar; Janakiraman, Ashok Kumar; Khalid, Syed Haroon; Ramanunny, Arya Kadukkattil; Xia, Yang (International Journal of Pharmaceutical Compounding, Inc., 2024)
Fast Melt Tablet (FMT) is a newer type of orally disintegrating tablet using the advantage of cocoa butter that melts at body temperature to achieve fast melting effect when the tablet is placed in oral cavity. However, oral disintegrating dosage form must have good palatability so that patients can accept it. The objective of this study is to taste mask a previously developed FMT containing memantine hydrochloride using artificial sweetener namely aspartame and acesulfame K and conduct a palatability study. Six formulations were developed and each sweetener was used at three level (10mg, 20mg and 30mg) to taste mask memantine hydrochloride in FMT. Formulation T7 was selected as the best taste masked formulation. Aspartame 30mg is sufficient to cover the bitter taste of memantine hydrochloride. A taste masked memantine hydrochloride FMT containing 30mg of aspartame was successfully developed. This formulation has hardness of 17.31 (0.18) Newton, 0.51 (0.02) g weight, 6.18 (0.42) mm thickness and in-vitro melting time of 31.16 (1.23) seconds. This novel dosage form has the potential to be commercialized as a patient friendly dosage form to treat Alzheimer’s disease.